(untitled) (International Journal of Academic Research in Progressive Education and Development, 2022)
English is one of the most spoken languages in the world, and many people are making English their main or additional language. Learning English is even more important for university students as they need to use the language in a classroom setting to learn, communicate and participate. One of the most common ways of teaching English is using Oral Corrective Feedback. The purpose of this study is to identify the perspectives of ESL/EFL students on the effectiveness of Oral Corrective Feedback. This study employed a quantitative method by administering questionnaires to 82 English language students supported by qualitative data from 9 students. The quantitative data were analysed using the descriptive method and Spearman’s Correlation Analysis. The qualitative data were analysed thematically based on Lyster et al.’s (2013) interaction hypothesis and Dekeyser’s (2020) Skill Acquisition Theory. The result showed a relationship between the level of proficiency and the student’s perspective on whether they want their lecturers to correct their errors in speaking English. The results also indicated that different language proficiency resulted in different views on using OCF in the classroom. Students with advanced proficiency indicated that they do not prefer to use OCF in the classroom. However, it is also noted that other than the level proficiency, students’ background knowledge might have contributed to the student’s view on OCF. Several recommendations for future study have also been added in this study.